Informal care‐giving and mental ill‐health – differential relationships by workload, gender, age and area‐remoteness in a UK region. (18th October 2016) - Doebler, Stefanie; Ryan, Assumpta; Shortall, Sally; Maguire, Aideen
Abstract: Informal care‐giving can be a demanding role which has been shown to impact on physical, psychological and social well‐being. Methodological weaknesses including small sample sizes and subjective measures of mental health have led to inconclusive evidence about the relationship between informal care‐giving and mental ill‐health. This paper reports on a study carried out in a UK region which investigated the relationship between informal care‐giving and mental ill‐health. The analysis was conducted by linking three data sets, the Northern Ireland Longitudinal Study, the Northern Ireland Enhanced Prescribing Database and the Proximity to Service Index from the Northern Ireland Statistics and Research Agency. Our analysis used both a subjective measure of mental ill‐health, i.e. a question asked in the 2011 Census, and an objective measure, whether the respondents had been prescribed antidepressants by a General Practitioner between 2010 and 2012. We applied binary logistic multilevel modelling to these two responses to test whether, and for what sub‐groups of the population, informal care‐giving was related to mental ill‐health. The results showed that informal care‐giving per se was not related to mental ill‐health, although there was a strong relationship between the intensity of the care‐giving role and mental ill‐health. Females under 50, who provided over 19 hours of care, were not employed or worked part‐time and who provided care in both 2001 and 2011 were at a statistically significantly elevated risk of mental ill‐health. Caregivers in remote areas with limited access to shops and services were also at a significantly increased risk as evidenced by prescription rates for antidepressants. With community care policies aimed at supporting people to remain at home, the paper highlights the need for further research in order to target resources appropriately.